The Medicinal Plant Pair Bupleurum chinense-Scutellaria baicalensis – Metabolomics and Metallomics Analysis in a Model for Alcoholic Liver Injury - Dang, Zefang; Li, Qianhua; Sun, Shujun; Wang, Yang; Lin, Rui; Zhang, Yongyu; Dai, Jianye; Zheng, Ningning (Frontiers in Pharmacology, 2019)
Traditional Chinese Medicine (TCM), a complex natural herbal medicine system, has increasingly attracted attentions all over the world. Most researches illustrated the mechanism of TCM based on the active components or single herbs. It was fruitful and effective but far away from satisfaction as losing sights into the interactivity and combined effect. In this work, we used Bupleurum chinense (Bupleurum chinense DC, a species in the genus Bupleurum, family Apiaceae) and Scutellaria baicalensis (Scutellaria baicalensis Georgi, a species in the genus Scutellaria, family Lamiaceae), an herbal pair in TCM, to illustrate the combined effect. We compared the diverse effects between Bupleurum chinense-Scutellaria baicalensis herbal pair and its compositions in animal model of Alcoholic Liver Injury to highlight the advantages and connotation of formula. Biochemical and histological indicators revealed that the effect of Bupleurum chinense-Scutellaria baicalensis was better than its compositions. Furthermore, metabolites profiling of serum, liver tissue, and feces were conducted to reveal that the herbal pair largely presented its effects through enhanced tissue penetration to maintain liver-located intervention with less global and symbiotic disturbance. Furthermore, we analyzed the distribution of the metal elements in extraction, serum and liver tissue, and found that the herbal pair significant regulated the distribution of endogenous selenium in liver tissue. As selenium plays important role in the anti-oxidative and hepatoprotective effects, it may be the reason of combined effects in BS formula. This research could enlighten new perspective for exploring material basis of combined effect in natural herbal medicine.